2016
DOI: 10.1371/journal.pone.0168281
|View full text |Cite
|
Sign up to set email alerts
|

TET1 Depletion Induces Aberrant CpG Methylation in Colorectal Cancer Cells

Abstract: Aberrant DNA methylation is commonly observed in colorectal cancer (CRC), but the underlying mechanism is not fully understood. 5-hydroxymethylcytosine levels and TET1 expression are both reduced in CRC, while epigenetic silencing of TET1 is reportedly associated with the CpG island methylator phenotype. In the present study, we aimed to clarify the relationship between loss of TET1 and aberrant DNA methylation in CRC. Stable TET1 knockdown clones were established using Colo320DM cells, which express high leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 53 publications
1
12
0
1
Order By: Relevance
“…This is supported by the fact that in gastric cancer cells, TET1 binds to the hypermethylated PTEN and re-activates its transcription through the demethylation of its promoter (45). Furthermore, it has been suggested that the decreased expression of TET1 may induce aberrant DNA methylation (46). Indeed, we observed an increase in the level of methylation at the +27 CpG site.…”
Section: Discussionsupporting
confidence: 68%
“…This is supported by the fact that in gastric cancer cells, TET1 binds to the hypermethylated PTEN and re-activates its transcription through the demethylation of its promoter (45). Furthermore, it has been suggested that the decreased expression of TET1 may induce aberrant DNA methylation (46). Indeed, we observed an increase in the level of methylation at the +27 CpG site.…”
Section: Discussionsupporting
confidence: 68%
“…Genome wide DNA methylation was analyzed using an Infinium HumanMethylation450 BeadChip (Illumina, San Diego, CA, USA) as described [ 46 ]. The data were then assembled using GenomeStudio methylation software (Illumina) and analyzed using Microsoft Excel (Microsoft Corporation, Redmond, WA, USA) and JMP 11 (SAS Institute Inc., Cary, NC, USA).…”
Section: Methodsmentioning
confidence: 99%
“…CRC cell lines (CaCO2, Colo320, DLD1, HCT116, HT29, LoVo, RKO, SW48, SW480, SW620, T84, and WiDr), a breast cancer cell line (MCF7), and HEK293 cells were described previously [5456]. DLD1, RKO, MCF7, and HEK293 cells were maintained in DMEM supplemented with 10% fetal bovine serum.…”
Section: Methodsmentioning
confidence: 99%
“…Dot blot analysis was performed as described previously [56]. A mouse anti-5-methylcytosine (5-mC) monoclonal antibody (1:1000 dilution, catalog no 39649, Active Motif, Carlsbad, CA, USA) was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation